Co-segregation of trichorhinophalangeal syndrome with a t(8;13)(q23.3;q21.31) familial translocation that appears to increase TRPS1 gene expression - David, Dezső (2014)
Trichorhinophalangeal syndrome type I (TRPS I) is a rare autosomal dominant syndrome caused by haploinsufficiency of TRPS1 due to point mutations or deletions. Here we report the first familial TRPS I due to a t(8;13)(q23.3;q21.31) translocation breakpoint <100 kb from the 5’ end of TRPS1. Based on the additional abnormalities observed exclusively in the index patient that are mainly compatible with clinical features of TRPS, her phenotype was defined as expanded TRPS I including brain malformations and intellectual disability. Initial analyses did not reveal any genetic defect affecting TRPS1 or any genomic alteration within the breakpoint regions or elsewhere in the genome. The pathogenic chromosome 8q23.3 breakpoint is at position g.116,768,309_116,768,310 within a transposon type I element, 87 kb from the TRPS1 5’ end. The 13q21.31 breakpoint is within a tandem repeat region at position g.65,101,509_65,101,510 (genome assembly GRCh37/hg19). This breakpoint is flanked by protocadherin 9 (PCDH9) and protocadherin 20 (PCDH20). As an outcome of the translocation, an evolutionarily conserved non-coding VISTA enhancer element from 13q21.31 is placed within the TRPS1 5’ region, 1,294 bp from the breakpoint. The increased expression of TRPS1 found by three independent methods is most probably translocation allele derived and driven by the translocated enhancer element. The index patient’s expanded phenotype presumably involves the epithelial-to-mesenchymal transition pathway that may be due to TRPS1 overexpression. Together, these findings support that the reported translocation associated phenotypes are “cis-ruption” and TRPS1 overexpression related, the latter most probably caused by the novel enhancer element in the TRPS1 5’ region.